Crystal Structure of Helicobacter pylori Pseudaminic Acid Biosynthesis N-Acetyltransferase PseH: Implications for Substrate Specificity and Catalysis - Ud-Din, Abu I; Liu, Yu C.; Roujeinikova, Anna (PLOS ONE, 2015)
Helicobacter pylori infection is the common cause of gastroduodenal diseases linked to a higher risk of the development of gastric cancer. Persistent infection requires functional flagella that are heavily glycosylated with 5,7-diacetamido-3,5,7,9-tetradeoxy-L-glycero-L-manno-nonulosonic acid (pseudaminic acid). Pseudaminic acid biosynthesis protein H (PseH) catalyzes the third step in its biosynthetic pathway, producing UDP-2,4-diacetamido-2,4,6-trideoxy-β-L-altropyranose. It belongs to the GCN5-related N-acetyltransferase (GNAT) superfamily. The crystal structure of the PseH complex with cofactor acetyl-CoA has been determined at 2.3 Å resolution. This is the first crystal structure of the GNAT superfamily member with specificity to UDP-4-amino-4,6-dideoxy-β-L-AltNAc. PseH is a homodimer in the crystal, each subunit of which has a central twisted β-sheet flanked by five α-helices and is structurally homologous to those of other GNAT superfamily enzymes. Interestingly, PseH is more similar to the GNAT enzymes that utilize amino acid sulfamoyl adenosine or protein as a substrate than a different GNAT-superfamily bacterial nucleotide-sugar N-acetyltransferase of the known structure, WecD. Analysis of the complex of PseH with acetyl-CoA revealed the location of the cofactor-binding site between the splayed strands β4 and β5. The structure of PseH, together with the conservation of the active-site general acid among GNAT superfamily transferases, are consistent with a common catalytic mechanism for this enzyme that involves direct acetyl transfer from AcCoA without an acetylated enzyme intermediate. Based on structural homology with microcin C7 acetyltransferase MccE and WecD, the Michaelis complex can be modeled. The model suggests that the nucleotide- and 4-amino-4,6-dideoxy-β-L-AltNAc-binding pockets form extensive interactions with the substrate and are thus the most significant determinants of substrate specificity. A hydrophobic pocket accommodating the 6’-methyl group of the altrose dictates preference to the methyl over the hydroxyl group and thus to contributes to substrate specificity of PseH.